2021
DOI: 10.21203/rs.3.rs-1169768/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of Self-Neglect and Associated Factors Among Disability Elderly in China

Abstract: Purpose: To assess the prevalence of self-neglect and associated factors among disability elderly(age≥65 years) in China.Patients and methods: Patients aged 65 years or above were enrolled from two communities in Shenyang,China. A convenience sample of 230 disability elderly responded to the questionnaire survey. The data were collected by a series of questionnaires consisting of socio-economic and demographic characteristics, Barthel Index(BI), Elder Self-Neglect Assessment(ESNA), Geriatric Depression Scale-S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…In this study, social support demonstrated a negative association with self-neglect, which is consistent with previous studies. A prior Chinese study reported that older adults with disabilities who received more social support had a lower level of self-neglect and a more stable psychological state ( Dong and Sun, 2021 ). A qualitative study revealed nurses’ perception that limited social support exacerbates the severity of self-neglect ( Wu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, social support demonstrated a negative association with self-neglect, which is consistent with previous studies. A prior Chinese study reported that older adults with disabilities who received more social support had a lower level of self-neglect and a more stable psychological state ( Dong and Sun, 2021 ). A qualitative study revealed nurses’ perception that limited social support exacerbates the severity of self-neglect ( Wu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that SN was linked to higher levels of deprivation [26,33]. Furthermore, income and SN have also been shown to be related, with SN more common when income is lower [27,[34][35][36], though other SN studies contradict these findings [37,38]. Living alone was identified as being significantly more common in individuals who SN [27,39,40] and this was also found in the related condition of HD [28,41,42].…”
Section: Introductionmentioning
confidence: 99%